Detección de Bartonella spp. en gatos de barrios con necesidades básicas insatisfechas de la Ciudad Autónoma de Buenos Aires - Watanabe, O. (2020)
Species belonging to the genus Bartonella spp. are becoming increasingly important as emerging zoonotic pathogens worldwide. Although many of these species are hosted mainly by cats, there is scarce information about their circulation in these companion animals in Argentina. In this work, we describe the molecular detection of Bartonella henselae and Bartonella clarridgeiae in different samples (blood, oral swab and fleas) from cats owned by people with unmet basic needs from the southern region of Buenos Aires City. This research revealed a high prevalence of infection by B. clarridgeiae in all analyzed samples. Also, 31% of the sampled fleas yielded a positive result, which highlights the importance of their control to prevent the transmission of this infection among cats and indirectly prevent cat-scratch disease in humans.